Different pharmacoresistance of focal epileptic spasms, generalized epileptic spasms, and generalized epileptic spasms combined with focal seizures. Issue 1 (19th November 2021) - Takahashi, Yukitoshi; Ota, Akiko; Tohyama, Jun; Kirino, Tomoko; Fujiwara, Yumi; Ikeda, Chizuru; Tanaka, Shigeki; Takahashi, Jyunya; Shinoki, Toshihiko; Shiraga, Hiroshi; Inoue, Takushi; Fujita, Hiroshi; et al.
Abstract: Objective: Among standard treatments for infantile spasms, adrenocorticotropic hormone (ACTH) is reported as the best treatment, but ACTH is ineffective in one‐half of the patients. To establish precision medicine, we examined pharmacoresistance of focal epileptic spasms (ES), generalized ES, and generalized ES combined with focal seizures, diagnosed based on the revised seizure classification of ILAE in 2017. Methods: We conducted a retrospective nationwide study in Japan on the long‐term seizure outcome of ES. Long‐term seizure outcome was evaluated by seizure‐free rate, seizure‐free period, and Kaplan‐Meier curve. Seizure‐free was defined as seizure control for longer than 2 months. Results: From the medical history of 501 patients, 325 patients had generalized ES only (GES group) at the start of the first treatment, 125 patients had generalized ES after focal seizure onset (FS‐GES group), seven patients had focal ES after focal seizure onset (FS‐FES group), and 24 patients had generalized ES combined with focal seizures after focal seizure onset (FS‐GES + FS group). Seizure‐free period of ES (generalized ES and focal ES) [mean (95% confidence interval)] was 2.7 (0.0‐5.4) months in GES group, 1.1 (0.1‐2.2) months in FS‐GES group, 1.0 (0.2‐1.9) months in FS‐GES + FS group, and 0.1 (−0.2‐0.5) months in FS‐FES group. Seizure‐free rate, seizure‐free period, and Kaplan‐Meier curve of generalized ES were almost the same in GES group and FS‐GES group, with characteristics of superior response to ACTH. Mean seizure‐free period of generalized ES combined with focal seizures was significantly shorter in FS‐GES + FS group than in GES group. Mean seizure‐free period of focal ES in FS‐FES group was extremely short with exceedingly early relapse. Significance: Pharmacoresistance was different in generalized ES, focal ES, and generalized ES combined with focal seizures. ES with focal features or with focal seizures may have focal lesions, thus consider surgical options earlier in the course.